Visible-light photoelectric performance of RMnO3 (R = La, Pr and Nd) epitaxial films with structural distortion. Issue 14 (15th July 2022) - Yang, Jiacheng; Liu, Haifeng; Wang, Lin; Li, Jie; Sun, Yuxi; Xie, Ruishi; Guo, Baogang; Zhang, Xingquan; Wen, Yahui; Zheng, Kui; Huo, Jichuan
Abstract: All-inorganic perovskite has aroused extensive attention as the light absorption layer of solar cells due to the high photoelectric conversion efficiency and chemical stability. In this work, RMnO3 (RMO, R = La, Pr and Nd)/(001) LaAlO3 (LAO) epitaxial films were prepared by the polymer assisted deposition method. All of the RMO films were grown epitaxially with tetragonal distortion (like Jahn-Taller distortion) of MnO6 octahedron. Owing to lattice mismatch between RMO and LAO, the tetragonal distortion of MnO6 octahedron increases when the radius of trivalent R ions increases. This reduces the crystal field splitting energy of MnO6 octahedron, resulting in a reduction in the band gap and enhancement of the visible-light photoelectric performance. It also reveals that the surface-adsorbed oxygen plays a crucial role in the photoelectric process of the RMO epitaxial films. More surface-adsorbed oxygen, existing in RMO films with larger R ions, can enhance the double exchange of electrons in Mn 3+ - O 2− - Mn 4+, thus preventing the recombination of photogenerated electron-hole pair and improving the photoelectric performance. These results provide a channel to tune the structure and photoelectric performance of perovskite manganese oxide.